Pengembangan Modul Dukungan Suami untuk Mencapai Keseimbangan Kerja-Keluarga - Arri Handayani; Primaningrum Dian M (Faculty of Psychology, Universitas Semarang, 2021)
This study is a development using Borg and Gall model. It aims to compile module on husband support to achieve work-family balance for working mothers. The researcher involved 15 respondents for initial data collection, 30 respondents for the small group trial, and 4 judgment experts (family psychology, industrial psychology, Himpaudi research and development, and media). For the big group, there were 50 respondents involved. Data were collected using open and closed questioners and self-assessment scale. Data collected, both qualitative and quantitative, were then analyzed descriptively. Research results show that 1). The result of module validation shows that the layout and concept of the module is categorized as good with slight revision. However, this module is suitable for the training on husband support to achieve work-family balance. 2). The implementation of the module in both small and big group shows that the participants have shown improvement in their understanding and perception of husband support. This shows that husband support module compiled effectively can increase participants skill and understanding in achieving work-family balance.